2011
DOI: 10.1364/boe.2.001803
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the size and shape of a red blood cell on elastic light scattering properties at the single-cell level

Abstract: We demonstrate the use of a double-beam optical tweezers system to stabilize red blood cell (RBC) orientation in the optical tweezers during measurements of elastic light scattering from the trapped cells in an angle range of 5-30 degrees. Another laser (He-Ne) was used to illuminate the cell and elastic light scattering distribution from the single cell was measured with a goniometer and a photomultiplier tube. Moreover, CCD camera images of RBCs with and without laser illumination are presented as complement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(76 citation statements)
references
References 44 publications
(83 reference statements)
1
67
0
Order By: Relevance
“…Tycko et al [26] found good agreement in flow cytometric measurements of sphered RBCs with the Mie theory. More recently Kinnunen et al [35] have compared the scattering patterns from actual RBCs as well as from a spherical RBC with Mie results. Good correlation was found in comparisons of Mie theory and sphered RBCs.…”
Section: \ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tycko et al [26] found good agreement in flow cytometric measurements of sphered RBCs with the Mie theory. More recently Kinnunen et al [35] have compared the scattering patterns from actual RBCs as well as from a spherical RBC with Mie results. Good correlation was found in comparisons of Mie theory and sphered RBCs.…”
Section: \ Introductionmentioning
confidence: 99%
“…In fact, it is known that even the entire membrane contributes negligibly to the scattering properties of a RBC [26,30]. (ii) It has been observed that RBC volume and refractive index are the main factors in determining changes in scattering cross-sections and not the shape [35,36]. Thus, for blood in physiological concentrations, the Mie theory offers a good description of the absorption coefficient, even without sphering, in the spectral range 600 to 1100 nm where absorption is low [36].…”
Section: \ Introductionmentioning
confidence: 99%
“…It is evident that the orientation of the aggregate affects the near-field intensity distribution. As seen, the scattering intensity is much stronger than from single cells [29], due to the aggregate's larger scattering cross-section. By measuring the suspension's total refractive index and relative refractive index (m=n p /n t , where n p is the refractive index of the particle and n t is the total refractive index of the medium), we can estimate the effect of an additive on light scattering from a single particle.…”
mentioning
confidence: 87%
“…For RBCs, however, most of the published results have been obtained through an image analysis of intensity images [27], [28]. Our recent results show the potential of the goniometric method for single RBC level measurements [29]. In these experiments, RBCs were suspended in a filtered PBS suspension.…”
mentioning
confidence: 96%
“…Among them, we chose Mieplot 4.3 by Laven (2011), which supports the import of external refractive indices. Its reliability has been verified by many researchers (Riley et al 2004;Husted et al 2009;Shen and Wang 2010;Kinnunen et al 2011). The refractive index value of polystyrene was adopted from Palik (1991).…”
Section: Lts Theorymentioning
confidence: 99%